Self-organized titanium dioxide nanotube layers: influence of repetitive anodizations - Macák, Jan M.; Sopha, Hanna Ingrid; Knotek, Petr (TANGER, 2015)
In the present work we report on the influence of repetitive anodization cycles upon the dimensions and morphology of self-organized TiO2 nanotube layers. Electrolytes based on ethylene glycol (containing water and NH4F) and widely used Titanium thin foils as substrates were utilized. These substrates were repetitively anodized, a total 3 times, and the resulting layers were removed and analyzed after each anodization step. Investigations by SEM show that, overall, nanotubes within nanotube layers produced by the repetitive anodization on one identical substrate, grow so that the tube diameter becomes gradually smaller. In addition, investigations carried out by AFM and mechanical profilometry show that repetitive anodization lead to significant smoothing (or polishing) of initially coarse substrates – this aspect is somewhat surprisingly not discussed in the existing literature. As a result, before each new anodization step, the nanotube layers grow on gradually smoother substrates with positive implications on the overall nanotube layer uniformity.
Keywords: titanium dioxide; nanotubes; anodization; roughness; smoothening